Development and Implementation of the EU Grand Strategies : Sociological, Policy, and Regional Considerations of Agenda 2030. - Rončević, Borut; Gangaliuc, Cristian; Pandiloska Jurak, Alenka; Cepoi, Victor; Fric, Urska; Ursic, Erika; Besednjak Valič, Tamara (Frankfurt a.M. : Peter Lang GmbH, Internationaler Verlag der Wissenschaften, 2022)
The subject of this book are the challenging and exciting issues of the implementation of the European Union's grand strategies. The particular interest dedicates to the current Agenda 2030 and its Sustainable Development Goals and Agenda 2030 with Cultural Political Economy, especially on the basis of data collected during the SOE2030.
Streamline governance of research, development and innovation -- Enhanced cooperation between business and research -- Support to integrate the research, development and innovation organisations in Romania in the European Research Area -- Private sector aid schemes -- Establishment and operationalisation of Centres of Competence -- Development of a programme to attract highly specialised human resources from abroad in research, development and innovation activities -- 7. Open innovation towards EU's Green Deal circular economy goals: Can the Covid-19 epidemic be an opportunity to accelerate the achievement of goals? -- The timeline of circular economy legislation and actions: From the beginning to nowadays -- The timeline of open innovation legislation and actions: From the beginning to nowadays -- 8. Conclusions -- References -- About the Authors -- Table 1: Abbreviations -- Table 2: The EU Cohesion policies in data -- Table 3: The EU membership -- Table 4: EU Region development level -- Table 5: GDP per capita as indicator of development -- Table 6: Shares of GDP in industry among selected European countries -- Table 7: Employed in industry -- percentage of total employed -- Table 8: Innovation Scoreboard Comparison -- Table 9: The Comparative Table of 3O'S Strategy and EIS -- Table 10: Roadmap of EU policy documents.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books